Kultura masowa jako przestrzeń działania nauczyciela edukacji wczesnoszkolnej - Matusz-Rżewska, Alicja (Nauczyciel wczesnej edukacji: Rozwijanie kompetencji zawodowych, 2016)
The following considerations are an attempt to face the present, more and more prevalent phenomenon – mass culture, referred to as popular culture as well, which plays a significant role in the early childhood socialization process. It is also present in the life of those who are responsible for the generation growing up under their care. Therefore, it seems necessary for education organizers to be fully conscious while exploring this difficult and risky issue of mass culture. This is particularly important that children are uncritical in accepting what they are offered from the external world and are easily mesmerized by anything that is massive. The task of educators is then to consciously and critically participate in the culture which manipulates, mesmerizes and devours altogether.